THE FACTORS OF DIRECT INFLUENCE ON THE 21ST CENTURY INSTRUCTIONAL COMPETENCIES OF SECONDARY SCHOOL TEACHERS IN THE CATHOLIC DIOCESE OF CHENNAI, INDIA - UGERIUS HEARTY, REYNOLD FERNANDO; ASAVISANU, POONPILAS (Scholar: Human Sciences, 2022)
The purpose of this research was to determine the direct factors to enhance the 21st-century instructional competencies of secondary school teachers. Factors of direct influence are herein defined as events, decisions, or situations that influence teaching and learning. The research objectives focused on: (1) finding the ideal 21st-century instructional competencies and the factors that influence those competencies, (2) developing a survey instrument for the assessment of the factors influencing 21st-century instructional competencies of school teachers in southern India, and (3) finding the relationships that exist between the factors influencing 21st-century instructional competencies of secondary school. A simple random sampling of books and journals published between 1999 and 2020 on instructional competencies provided the data for the qualitative content analysis. A survey instrument was constructed using the findings. For the third objective, data collection was done using the survey instrument and then analyzed using advanced statistical methods. The analysis found a Pearson’s Coefficient (r) of .641, with a p-value of .000, indicating a strong positive relationship between the 21st-century instructional competencies (TFCIC) and the factors identified. The findings of this study showed that there were seven statistically significant factors that predict the 21st-century instructional competencies, F (7, 411) = 49.768, p < .001, proving that the regression model was a good fit for the data provided. The regression analysis determined the direct factors influencing 21st-century instructional competencies of secondary school teachers, as identified as student-centered approaches, use of information technology, school policies of teaching and learning statistically significant at p<.001, and student participation statistically significant at p<.05. This study proposes recommendations for best instructional practices of secondary school teachers that are suited for 21st-century education.